2009
DOI: 10.1017/s0022215109005039
|View full text |Cite
|
Sign up to set email alerts
|

Repair with sternohyoid muscle fascia after subtotal laryngectomy

Abstract: Sternohyoid muscle fascia reconstruction leads to optimal repair of subtotal laryngectomy defects and restored laryngeal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In previous studies, the sternohyoid muscle was reported to be used for reconstruction of larynx or repair of laryngotracheoesophageal cleft without any adverse effect of neck movement. 8 10) For this case, the defect of esophagus was adjacent to the origin of left sternohyoid muscle; thus, we used the left sternohyoid muscle flap to repair the defect of the esophagus.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the sternohyoid muscle was reported to be used for reconstruction of larynx or repair of laryngotracheoesophageal cleft without any adverse effect of neck movement. 8 10) For this case, the defect of esophagus was adjacent to the origin of left sternohyoid muscle; thus, we used the left sternohyoid muscle flap to repair the defect of the esophagus.…”
Section: Discussionmentioning
confidence: 99%
“…In 18 of the patients, the tracheostomy cannula could not be removed. Dong et al (2009) conducted a case series including 39 patients with cancer of the supraglottic larynx or piriform sinus. The supraglottis was reconstructed with a sternohyoid myofascial flap and 13 of 39 patients had a persisting airway stenosis depending on a tracheostomy cannula.…”
Section: Discussionmentioning
confidence: 99%
“…(Figure 7 ) The muscle group is expected to survive on the presence of the dominant pedicle, comprised of the cranial thyroid and superficial cervical arteries. 16 These muscles have been used to reconstruct the larynx in humans following subtotal laryngectomy 17 and laryngo‐tracheostomy 18 and to reconstruct total glossectomies in humans with tongue cancer. 19 In dogs, a similar muscle flap has been used experimentally to reinforce a tracheal end‐to‐end anastomosis 20 and to patch esophagotomy sites.…”
Section: Discussionmentioning
confidence: 99%